Meritocracy-its place in Singapore society - Juliana June Rasul (2008)
Meritocracy has long been a pillar for Singapore society. In its quest to seek out the best and the brightest to lead the country, has it forgotten those who haven’t been able to keep up? In this four-part feature, we examine the conse-quences of being a meritocractic society.